YOUTH READINESS FOR DIGITALIZATION OF THE ECONOMY - Skosyreva, Nina; Zinich, Alla; Pomogaev, Vitalii; Revyakina, Yulia; Vasyukova, Marina; Avlasovich, Elena (Revista Inclusiones, 2020)
The article deals with the problem of the modern youth readiness to live and work in the new economic realities caused by the digitalization of the economy and other spheres of society. The authors focus on the contradictory nature of this process, which, on the one hand, spreads inevitably, objectively, regardless of subjective factors, rapidly, intensively and extensively, and on the other hand, the effectiveness and constructiveness of its movement are directly related to the human factor, the level of readiness and ability of the subject to be an active participant in this process and influence it. The article substantiates the need to form a set of new competencies necessary for participants in the transformation of modern society into digit-based informationoriented society. The article analyzes the results of a sociological study conducted in 2020 at the Omsk State Agrarian University named after P. Stolypin, during which 1,188 respondents were interviewed.